East-West relations : is detente possible? - Griffith, William E.; Rostow, Walt W. (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1969)
In the East- West Relations: Is Détente possible, the authors tries to analyze the possibility of ease of tension between the East countries and the West countries considering the kind of relationship that has existed between the them.
"Rational debate seminars".
Includes bibliographical references.
gp 21/01/2019
Loans
Keywords: World politics